1997
DOI: 10.1007/s004030050258
|View full text |Cite
|
Sign up to set email alerts
|

Altered catecholamine synthesis and degradation in the epidermis of patients with atopic eczema

Abstract: Patients with atopic eczema have significantly higher norepinephrine levels in plasma than healthy controls. In addition, significantly higher levels of the essential cofactor (6R)-L-erythro-5,6,7,8-tetrahydrobiopterin (6BH4) were found in this patient group. Cell extracts from epidermal suction blister roofs revealed only half the normal activity of phenylethanolamine-N-methyl transferase (PNMT) together with a threefold induction of the norepinephrine-degrading enzyme monoamine oxidase A (MAO-A). Taken toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…The role of the b-adrenergic receptor system in the pathophysiology of vascular events during AD is still controversial. 1 In AD the T H 1-T H 2 paradigm has been central to interpreting quantitative differences in cytokine expression in response to environmental stimuli or stress. 2,3 In addition, other mechanisms (eg, oxidative stress pathways, glucocorticoid resistance, nerve-mast cell interactions, and intestinal dysbiosis) and a broader range of mediators (eg, chemokines, amines, oxidative products, proteases, and neuropeptides) produced by cells communicating with the dermal vasculature might be involved, delineating the true complexity of the mechanisms linking stress to AD (Fig 1).…”
Section: Neurovascular Interactions In Atopic Dermatitismentioning
confidence: 99%
“…The role of the b-adrenergic receptor system in the pathophysiology of vascular events during AD is still controversial. 1 In AD the T H 1-T H 2 paradigm has been central to interpreting quantitative differences in cytokine expression in response to environmental stimuli or stress. 2,3 In addition, other mechanisms (eg, oxidative stress pathways, glucocorticoid resistance, nerve-mast cell interactions, and intestinal dysbiosis) and a broader range of mediators (eg, chemokines, amines, oxidative products, proteases, and neuropeptides) produced by cells communicating with the dermal vasculature might be involved, delineating the true complexity of the mechanisms linking stress to AD (Fig 1).…”
Section: Neurovascular Interactions In Atopic Dermatitismentioning
confidence: 99%
“…Failure to evoke normal inhibition of cell division of basal cells thus seems plausible in the pathogenesis of epidermal hyperproliferation seen in atopic dermatitis. While some investigators proposed that there might be lower densities of beta2 adrenergic receptors in undifferentiated keratinocytes [44], there is limited evidence of this, and in fact, other investigators have found normal adrenoceptor densities but lower receptor binding affinities, albeit on lymphocytes [45]. Nonetheless, these early studies have provided provocative evidence suggesting the involvement of beta adrenoceptors as contributing to the pathogenesis of atopic dermatitis.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Focusing on the keratinocyte defects, Schallreuter and colleagues have demonstrated that cell extracts from epidermal suction blister roofs of the uninvolved skin of atopic dermatitis patients have a significantly increased concentrations of norepinephrine and the cofactor (6R)-Lerythro-5,6,7,8,-tetrahydrobiopterin (6BH4), required for the conversion of L-phenylalanine to L-tyrosine, and for the subsequent conversion of L-tyrosine to L-dopa-two of the early steps in the catecholamine synthetic pathway (Figure 2), compared to aged-matched controls [44]. In addition, in this study there was a parallel threefold induction of the catecholamine degrading enzyme monoamine oxidase-A (MAO-A) activity with half the normal activity of the enzyme phenylethanolamine-N-methyl transferase (PNMT) required for conversion of norepinephrine into epinephrine (figure 2) in patients with atopic dermatitis.…”
Section: Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…In atopic dermatitis, abnormalities of the adrenergic system are not limited to receptors. Plasma levels of catecholamines are higher because of abnormalities in synthesis and degradation [63]. Immunoregulation under stressful conditions is ineffective in patients with atopic conditions, leading to aberrant immune responses and subsequent exacerbation of the disease [36,64].…”
Section: Hpa Axis In Atopic Dermatitismentioning
confidence: 99%